Implementasi Kebijakan Peraturan Otoritas Jasa Keuangan (POJK) No.11/Pojk.03/2020 dalam Menekan Non Performing Financing pada Perbankan Syariah - Fatkhur Rohman Albanjari; Catur Kurniawan (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2022)
The Coronavirus Disease-19 pandemic is an outbreak that has hit the world, with no exception for Indonesia. Many things are harmed from all aspects of life ranging from political, social, cultural, religious and economic fields. It also has an impact on the melemamahnya sharia banking system in Indonesia. This research has the purpose of knowing how the Financial Services Authority Regulation Policy (POJK) No.11/POJK.03/2020 in Suppressing Non Performing Financing (NPF) in Sharia Bank. This study uses narrative qualitative research methods with primary data from various electronic media, journals, and books, and related sources. The results of this study show that banks can implement policies that can support economic growth for sharia bank financing customers affected by the spread of Covid-19. Customers who get a restructuring waiver policy are customers affected by Covid-19 directly or indirectly.